Effect of Bench Press Exercise and Triceps Strength Bullet Rejection Ability to be Reviewed from the Flexibility of the Togok to FIK UNM Makassar Students - Anto Sukamto; Hikmad Hakim; Rahma Dewi; Nurkadri; Fransen Sinaga (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Fiction UNM Makassar student. The design used in this study is an experimental method using a 2x2 factorial design. This method is a test (validation) that is testing the effect of one or more variables on other variables. Factorial design is a research design by modifying the post-test-only control or pretest-posttest control group and the researcher adds other variables. The results of the research through hypothesis testing show that Farithmetic between columns (FA) = 26,444, looks bigger than = 4.113, it appears that > or P-value = 0.000 < 0.05 so H0 rejected and H1 accepted. Thus it can be concluded that overall there is a significant difference in the effect between bench press training and triceps strength on O'Brien's shot put ability to FIK UNM Makassar Students. interaction (FAB) = 163.155 and  = 4.113, it appears that > or P-value = 0.000 < 0.05, so H0 rejected and H1 accepted. In other words, it can be stated that the achievement of the O'Brien style shot put ability is influenced by the interaction between the training method and the flexibility of the togok.